Highly selective adsorption of perfluorinated greenhouse gases by porous organic cages - Tian, Ke; Elbert, Sven; Hu, Xin-Yue; Kirschbaum, Tobias; Zhang, Wen-Shan; Rominger, Frank; Schröder, Rasmus R.; Mastalerz, Michael (Advanced materials, 2022)
Anthropogenic greenhouse gases contribute to global warming. Among those gases, perfluorocarbons (PFCs) are thousands to tens of thousands of times more harmful to the environment than comparable amounts of carbon dioxide. To date, materials that selectively adsorb perfluorocarbons in favor of other less harmful gases have not been reported. Here, a series of porous organic cage compounds with alkyl-, fluoroalkyl-, and partially fluorinated alkyl groups is presented. Their isomorphic crystalline states allow the study of the structure-property relationship between the degree of fluorination of the alkyl chains and the gas sorption properties for PFCs and their selective uptakes in comparison to other, nonfluorinated gases. By this approach, one compound having superior selectivities of PFCs versus N2 or CO2 under ambient conditions is identified.